The Wolves of Mercy Falls: Linger - Book 2 - Stiefvater, Maggie 1981- (New York : Scholastic Press, 2010)
As Grace hides her deep love for Sam from her parents and Sam struggles to release his werewolf past and claim a human future, a new wolf named Cole wins Isabel's heart, but his own past threatens to destroy the whole pack.
Keywords: Wolves -- Fiction; Metamorphosis -- Fiction; Supernatural -- Fiction; Love stories